2007
DOI: 10.1097/01.tp.0000281409.35702.53
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Social Participation in the First Year After Kidney Transplantation: A Prospective Study

Abstract: We found that mainly clinical factors were associated with an increase in participation in society. Although health-status related factors and the psychological attribute self-efficacy may be related to recovery of social participation, their effect was outweighed by the strength of clinical predictors in multivariate analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…The baseline data collection wave (T1) was performed at 3 months and the second wave (T2) at 1 year posttransplantation [14]. For the third wave (March and April 2009; >6 years posttransplantation), eligibility assessment of the T2 study group ( n  = 58) showed that four recipients (7%) had died, three recipients (5%) were back on dialysis, and two (3%) had expressed unwillingness to participate in future studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The baseline data collection wave (T1) was performed at 3 months and the second wave (T2) at 1 year posttransplantation [14]. For the third wave (March and April 2009; >6 years posttransplantation), eligibility assessment of the T2 study group ( n  = 58) showed that four recipients (7%) had died, three recipients (5%) were back on dialysis, and two (3%) had expressed unwillingness to participate in future studies.…”
Section: Methodsmentioning
confidence: 99%
“…In 2002, we started a follow-up study among renal transplant recipients which aimed to describe changes in social participation (i.e., work, education, household tasks, leisure activities) in the first year after transplantation [14]. Considering work status, we found a rather stable employment rate during the first year after transplantation indicating that those who were able to maintain their job before transplantation did return to work.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, several predictors of not being employed post-Tx in kidney patients have been identified: Post-Tx employment status was consistently and highly correlated with pre-Tx employment status [47, 911]. Receiving a kidney from a living donor was regularly found to enhance social participation [12] and to specifically enhance the chance to be employed [6, 9, 13, 14]. Transplanted populations in general represent an aging population and most of these patients have a long disease history.…”
Section: Introductionmentioning
confidence: 99%
“…Indicators for complications [16], post-operative complications [6], comorbidity [12], and blood pressure [4] showed no influence on employment post-Tx. Findings with respect to the influence of creatinine on employment post-Tx are mixed [4, 12]. In recent studies, a negative influence of the duration of dialyses pre-Tx and a positive influence of pre-emptive Tx on employment have been reported [6, 9].…”
Section: Introductionmentioning
confidence: 99%
“…29,31 Aasebo 31 presented in a study about 'the life situation of kidney recipients' that kidney recipients had a higher education compared to the general population. Similar studies by Karam et al 11 and Van Der Mei et al 32 showed the opposite, that fewer liver-as well as kidney recipients had a higher education than the general population. Karam et al 19 also showed that higher education is associated with higher social participation.…”
Section: Educationmentioning
confidence: 72%